Gifts that Recalibrate Relationships: Marriage Prestations in an Arab Liberation Movement. Issue 2 (15th March 2018) - Wilson, Alice
ABSTRACT: Enduring scholarly interest in the social relations of gift exchange has, following Mauss, emphasised how gifts make relationships. Where gifts break relationships, their ethnographic distinctiveness has reinforced the wider notion that gifts are good at making relations. This article examines gifts which, without the empirical distinctiveness of gifts that break relationships, both make and break relationships. Speakers of the Hassaniya dialect of Arabic in north-west Africa give post-marital gifts from the bride's to groom's party; these gifts became highlighted amongst Sahrawi refugees in Algeria, on whom the article focuses. In addition to performing reciprocity, boosting the giver's honour and making new affinal relations, these post-marital gifts also break the relationship between the bride's family and the bride. The article argues that gifts' potential to recalibrate relationships through both making and breaking relationships can be helpfully incorporated into wider thinking about gifts, alongside other distinctions amongst gifts and gift relations.